i'm supposed to prove (p → q) ∧ (¬p → r) ⇒ (q ∨ r) with a truth table and im stuck. i've created most of the truth table by hand. but i do no know how to prove or disprove it.
any help is much appreciated.
Hello, nehal234!
I don't understand your difficulty.
. .i'm supposed to prove (p → q) ∧ (¬p → r) ⇒ (q ∨ r) with a truth table and im stuck.
i've created most of the truth table by hand. . Most if it? . . . What does that mean?
But i do no know how to prove or disprove it. . Do you understand what a truth table does?